Local prothoracic auditory neurons in Ensifera - Cillov, Ali; Stumpner, Andreas (Frontiers in Neuroscience, 2022)
A new method for individually staining insect neurons with metal ions was described in the late 60s, closely followed by the introduction of the first bright fluorescent dye, Lucifer Yellow, for the same purpose. These milestones enabled an unprecedented level of detail regarding the neuronal basis of sensory processes such as hearing. Due to their conspicuous auditory behavior, orthopterans rapidly established themselves as a popular model for studies on hearing (first identified auditory neuron: 1974; first local auditory interneuron: 1977). Although crickets (Ensifera, Gryllidae) surpassed grasshoppers (Caelifera) as the main model taxon, surprisingly few neuronal elements have been described in crickets. More auditory neurons are described for bush crickets (Ensifera, Tettigoniidae), but due to their great biodiversity, the described auditory neurons in bush crickets are scattered over distantly related groups, hence being confounded by potential differences in the neuronal pathways themselves. Our review will outline all local auditory elements described in ensiferans so far. We will focus on one bush cricket species, Ancistrura nigrovittata (Phaneropterinae), which has the so-far highest diversity of identified auditory interneurons within Ensifera. We will present one novel and three previously described local prothoracic auditory neuron classes, comparing their morphology and aspects of sensory processing. Finally, we will hypothesize about their functions and evolutionary connections between ensiferan insects.